Wind Turbine Assessment: A Step-by-Step Approach - Balo, Figen; Sua, Lutfu S. (wiley, 2024)
The weighted sum approach is suggested in this work as a multi-attribute decision-support strategy for the wind turbine selection problem. The inherent constraints of earlier investigations served as the inspiration for the suggested approach. These restrictions resulted from the use of computationally challenging methodologies, a lack of diversity of wind turbines, and simple decision models with a single criterion. Analytic hierarchy strategy is a methodology that is utilized to overcome various decision-making difficulties. Because it takes into account both intangible and tangible attributes, the analytic hierarchy strategy is popular for providing answers to multi-criteria problems. This strategy is used in the study to predict the factor weights and determine the elements’ relative weights involved in the wind turbine evaluation. Application of the suggested strategy to several types of wind turbines from various manufacturers is used for an analysis of the effectiveness of the approach. This research considers the participation of major elements in selecting a wind turbine for a wind facility in Turkey in order to build sustainable development management solutions. In this regard, an analytic hierarchy strategy was used to balance and choose the best alternative for the criteria and sub-criteria after calculating the significant aspects in the evaluation of a wind turbine technology in accordance with the principles of sustainable development management. Based on the findings, the most optimum alternative is determined as the top choice. © 2024 Scrivener Publishing LLC.
Keywords: electric sector’s sustainable development; MCDM; renewable energy; wind energy; wind turbine selection